2004
DOI: 10.5688/aj680358
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Distance Learning Using Videoconferencing Technology on Student Performance

Abstract: Objectives. To compare outcomes of distance education using interactive videoconferencing vs on-site education in pharmacotherapy courses. Methods. Four third-year required pharmacotherapy courses (Integumentary, Bone and Joint Disorders, Neurology, and Psychiatry) were offered locally (Amarillo, Tex) and at a distance (Lubbock, Tex, and Dallas, Tex) by interactive videoconferencing. To assess if students at distant sites are at a disadvantage, grade point averages (GPAs) before course enrollment and final gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 5 publications
7
45
0
4
Order By: Relevance
“…MacLaughlin and colleagues evaluated differences in learning outcomes in these third-year pharmacotherapy courses between local and distant students. 3 Learning outcomes were not significantly different for any of these pharmacotherapy courses between the host site (face-toface learning in a classroom setting) and remote sites.…”
Section: Introductionmentioning
confidence: 85%
“…MacLaughlin and colleagues evaluated differences in learning outcomes in these third-year pharmacotherapy courses between local and distant students. 3 Learning outcomes were not significantly different for any of these pharmacotherapy courses between the host site (face-toface learning in a classroom setting) and remote sites.…”
Section: Introductionmentioning
confidence: 85%
“…Of the 127 degree programs with accreditation status from the Accreditation Council of Pharmacy Education, 31 have a branch or distance education campus. 1 While the effectiveness of distance education relative to traditional education in pharmacy colleges and schools is well-established, [2][3][4][5][6] distance education presents unique challenges for students and instructors. In general, student isolation and attrition in distance education is associated with a lack of interaction between instructors, learners, and learning material.…”
Section: Introductionmentioning
confidence: 99%
“…The Amarillo, Lubbock, and Dallas campuses of Texas Tech School of Pharmacy, which use a synchronous teaching format to deliver the pharmacotherapeutic courses to all sites, found that the performance of students at local and distant sites were similar. 11,12 The studies were carried out during the third year of the pharmacy program, when students were distributed among the 3 campuses after spending the first 2 years in Amarillo. Additionally, equivalent performance of firstyear students in Anatomy and Pharmaceutical Calculations was found at the distant campus in Abilene and the local site in Amarillo during the 2007-2008 academic year.…”
Section: Discussionmentioning
confidence: 99%